Isoflavones and rotenoids from the leaves of Millettia brandisiana - Orasa Pancharoen (2018)
A new isoflavone, 4′-γ,γ-dimethylallyloxy-5,7,2′, 5′-tetramethoxyisoflavone, brandisianin A (1), was isolated from the leaves of Millettia brandisiana, along with one synthetically known isoflavone, 7,4′-di-O-prenylgenistein (2) and twelve known compounds. The structures were elucidated on the basis of extensive spectroscopic analysis. Two isolated compounds were tested for anti-inflammatory activity; 12a-hydroxy-α- toxicarol (11) showed significant anti-inflammatory activity. © 2008 Pharmaceutical Society of Japan.